PRESERVATION AND CONSERVATION OF INFORMATION RESOURCES: EVIDENCE- BASED FROM SOUTHERN DELTA UNIVERSITY LIBRARY, DELTA STATE - Aliyu, Muhammed’Rabiu (Current Journal of Library and Information Sciences (CJLIS), 2025)
The library plays a pivotal role in empowering information professionals and promoting national development. Through structured curricula, library schools provide librarians with the necessary knowledge and skills to effectively manage information resources, promote information literacy, support research and scholarship, preserve cultural heritage, promote lifelong learning and bridge the digital divide. This study aims to identify Preservation and Conservation Information Resources in the Southern Delta University Library. Three purposes of the study were formulated to guide the study. A descriptive survey design was used in the study. The study population consisted of sixteen (16) librarians from Southern Delta University Library, and an enumerative technique was used due to the sample size. The sample size of the study is sixteen (16). The instrument used to obtain information was a structured questionnaire, and the data collected were analyzed using the mean. The findings revealed that library security is the most widely used measure of preservation and conservation practices. Dust and particulate matter are the greatest causes of library material deterioration. The findings further revealed that dusting, cleaning, and proper shelving are the major techniques adopted by libraries. The study concluded that a lack of proper preservation and conservation practices in universities is the cause of resource loss and deterioration. Therefore, the study recommended that libraries deploy modern preservation and conservation tools such as technologically enabled ICT devices, which will aid in adequate storage and enhance the durability and longevity of information materials in libraries.